Circulating donor-derived cell-free DNA as a marker for rejection after lung transplantation - Li, Yunhui; Liang, Bin (Frontiers in Immunology, 2023)
Objective Recently, circulating donor-derive cell free DNA (dd-cfDNA) has gained growing attention in the field of solid organ transplantation. The aim of the study was to analyze circulating dd-cfDNA levels in graft rejection, ACR and AMR separately for each rejection type compared with non-rejection, and assessed the diagnostic potential of dd-cfDNA levels in predicting graft rejection after lung transplantation. Methods A systematic search for relevant articles was conducted on Medline, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang databases without restriction of languages. The search date ended on June 1, 2023. STATA software was used to analyze the difference between graft rejection, ACR, AMR and stable controls, and evaluate the diagnostic performance of circulating dd-cfDNA in detecting graft rejection. Results The results indicated that circulating dd-cfDNA levels in graft rejection, ACR, and AMR were significantly higher than non-rejection (graft rejection: SMD=1.78, 95% CI: 1.31-2.25, I2 = 88.6%, P< 0.001; ACR: SMD=1.03, 95% CI: 0.47-1.59, I2 = 89.0%, P < 0.001; AMR: SMD= 1.78, 95% CI: 1.20-2.35, I2 = 89.8%, P < 0.001). Circulating dd-cfDNA levels distinguished graft rejection from non-rejection with a pooled sensitivity of 0.87 (95% CI: 0.80-0.92) and a pooled specificity of 0.82 (95% CI: 0.76-0.86). The corresponding SROC yield an AUROC of 0.90 (95% CI: 0.87-0.93). Conclusion Circulating dd-cfDNA could be used as a non-invasive biomarker to distinguish the patients with graft rejection from normal stable controls. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023440467.